A clinicoepidemiological study of dermatoses among paediatric population - Sharma, Rohini; Abrol, Sameer (International Journal of Research in Medical Sciences, 2018)
Background: Alike the normal population, even paediatric population encounters various dermatological conditions. Dermatosis among paediatric population can range from acute conditions, to chronic or recurrent and does carry significant burden on quality of life. It has to be dealt separately from adults as it has different symptoms, requires different treatment as has different prognosis for the same disease as compared to adults. Aim was to study the clinico-epidemiological profile of various dermatoses prevalent among the paediatric population less than 18 years. Methods: This was a prospective study done at a tertiary care centre of Jammu region. Paediatric patients less than 18 years of age attending the dermatology outpatient department were taken up for study. A detailed history was taken from the patient or attendants, detailed clinical examination was done. Also, laboratory investigations like KOH, gram stain, AFB stain, woods lamp, histopathological studies among others were done wherever required. The results were statistically evaluated and inferences drawn. Results: A total of 600 children were taken up for study. Males outnumbered the females with 302 females and 298 males. Maximum no. of patients (36.8%) were in the 6-11 years age group followed by 1-5 years age group (27%). Most common dermatoses seen over all the age groups was infections and infestations (39.1%) followed by eczematous group (16%). However, the pattern of dermatoses did vary in each age group and also was determined by the climate. Many patients had more than one dermatoses. Conclusions: This study was done to assess the burden of dematoses among paediatric population and found that various dermatoses did vary according to various age groups. Infections and infestations formed a major share.